1983
DOI: 10.1038/ki.1983.203
|View full text |Cite
|
Sign up to set email alerts
|

Cell renewal of glomerular cell types in normal rats. An autoradiographic analysis

Abstract: Normal adult Sprague-Dawley rats received either a single or repetitive injection of the DNA precursor 3H-thymidine (3H-TdR). For autoradiography semi-thin sections were prepared 2 hr to 14 days after labeling. The majority of labeled cells noted in glomerular tufts were endothelial cells. Mesangial cells had a lower production rate. Podocytes revealed no evidence of proliferation. Bowman's capsule cells showed a higher labeling index than tuft cells at all times. Neither the urinary nor the vascular pole was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
107
2
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(113 citation statements)
references
References 11 publications
3
107
2
1
Order By: Relevance
“…35 In the present study, the dramatic upregulation of CCPs observed in glomerular endothelium of human IgAN biopsy specimens suggests a substantially increased turn-over rate of glomerular endothelial cells in addition to mesangial cell proliferation. The increase in CDK2 expression by glomerular endothelium observed in IgAN together with the increased CDK2 expression during mesangial cell proliferation reported in anti-Thy1.1 nephritis, 3 support the notion that the in vivo expression of certain cell cycle proteins may differ from that described in nonrenal cells studied in vitro.…”
Section: Discussionmentioning
confidence: 72%
“…35 In the present study, the dramatic upregulation of CCPs observed in glomerular endothelium of human IgAN biopsy specimens suggests a substantially increased turn-over rate of glomerular endothelial cells in addition to mesangial cell proliferation. The increase in CDK2 expression by glomerular endothelium observed in IgAN together with the increased CDK2 expression during mesangial cell proliferation reported in anti-Thy1.1 nephritis, 3 support the notion that the in vivo expression of certain cell cycle proteins may differ from that described in nonrenal cells studied in vitro.…”
Section: Discussionmentioning
confidence: 72%
“…In support of this is the estimate of 1% daily renewal made by Pabst and Sterzel. 12 Although we observed mesangial cells in all 5 mice revealing clonal hematopoietic engraftment, these numbers are too small to answer the question of whether or not all hematopoietic stem cells are capable of generating mesangial cells. Analysis of kidneys from mice receiving transplants of paired progenies of stem cells is in progress to examine the mechanisms of stem cell commitment to the mesangial cell lineage.…”
Section: Discussionmentioning
confidence: 84%
“…Previously, autoradiographic studies have demonstrated low rates of glomerular mesangial and endothelial cell proliferation in control rats, indicating low but constant rates of glomerular cell renewal of about 1% per day. 28 Our data suggest that bone-marrow-derived cells contribute to normal physiological glomerular-endothelial and mesangial cell turnover.…”
Section: Discussionmentioning
confidence: 89%